Hate speech in Malaysia : the necessity for specific legislation - Murni binti Wan Mohd Nor (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2015)
Hate speech has been an issue of heated debate amongst legal scholars and human rights activists. The need to guard free speech is important, but so is the need to protect the victim and to preserve public interest and peace within the society. The conflict between the exercising of individual liberty as opposed to collective rights becomes the primary focus of this research. In addressing the issue, fundamental theories of free speech was discussed first to determine if there are justifiable restrictions on free speech. The researcher also put forth an approach to interpreting human rights that may balance better between individual liberty and collective rights. In addition, reasons for regulating hate speech were briefly explained. The focus shifted to the Malaysian context by discussing the position of free speech and hate speech in the Federal Constitution, so as to determine if hate speech can and should be specifically legislated in Malaysia. In doing so, the grounds for limiting free speech provided for in the Constitution that could be applicable to hate speech were discussed. The researcher also explained the nature of race relations in Malaysia; taking into account the recent instances of racial and religious animosity as well as instances of hate speech that has addded fuel to the fire of tension of racial and religious tension. The researcher employed legal methodology, specifically doctrinaire analysis of primary and secondary documents. This research is reform oriented, whereby the researcher focused her evaluation on the existing problems surrounding a legal issue and suggest the necessary recommendations. Historical analysis of documents was also conducted on documents pre and post-Independence to ascertain the legal framework in Malaysia when it comes to free speech.The researcher has also conducted qualitative interviews with legal and human rights experts in order to ascertain whether hate speech should be specifically legislated against; and if so, what are the issues that need to be considered. At the end of the study, the researcher highlighted the dangers of hate speech on the individual, society and the state, which is why it is important to have a specific legislation on hate speech. The results of the interviews also supported the necessity of having a carefully drafted legislation. Lastly, the researcher put forth some recommendations of legal issues that need consideration if and when Malaysia is to have such a law. This research can be useful in the process of lawmaking and drafting of public policies, as the thesis highlighted an issue that is highly relevant and reflective of current events which shows the importance of having hate speech laws for the maintenance of racial and religious harmony. If a specific hate speech law is introduced after taking into account all the relevant legal issues, we may stand to have better protection against hate speech without transgressing unnecessarily on the individual's right to free speech.